The Relationship Between Parental Perception with Parental Participation in School Parenting Program in Asyiyah Bustanul Athfal Kindergarten Koto Taratak - Mega Meisisrika Aldi; Setiawati Setiawati (Universitas Negeri Padang, 2022)
The background of this research is the low participation of parents regarding the school parenting program at TK Aisyiyah Bustanul Atfhal Koto Taratak. This is due to the low perception of parents regarding the school parenting program. This research aims to: 1) Describe parents' perceptions of the school parenting program at TK Aisyiyah Bustanul Atfhal Koto Taratak. 2) Describe the participation of parents in the school parenting program at TK Aisyiyah Bustanul Atfhal Koto Taratak. 3) Seeing the relationship between parents' perceptions of the school parenting program and their participation in Aisyiyah Bustanul Atfhal Koto Taratak Kindergarten.This research was conducted with a quantitative approach to the correlational type. The population in this study were 35 people who were parents at TK Aisyiyah Bustanul Atfhal Koto Taratak, then the samples were taken using a stratified random sampling technique of 24 parents. The method of collecting data used a questionnaire with a list of statements format as a data collection tool, then the data was analyzed using a statistical percentage formula then to look for correlation using the Spearman Rho Formula.This study shows the results that: 1) An overview of parents' perceptions of the school parenting program at TK Aisyiyah Bustanul Atfhal Koto Taratak. 2) Description of participating in TK Aisyiyah Bustanul Atfhal Koto Taratak. 3) The relationship between parents' perceptions of the school parenting program and their participation in TK Aisyiyah Bustanul Atfhal Koto Taratak. Research suggestions are: 1) It is hoped that parents can participate actively in every activity that will be or is carried out at TK Aisyiyah Bustanul Atfhal Koto Taratak. 2) It is hoped that teachers can always invite parents to carry out school parenting program activities that can achieve success in learning for students at TK Aisyiyah Bustanul Atfhal Koto Taratak.Keywords: Perception, Parenting, Participation